1995
DOI: 10.1002/mus.880180708
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year experience in the treatment of focal movement disorders with low‐dose dysportTM botulinum toxin

Abstract: We report the results of botulinum toxin type A (Dysport, Porton Products, UK) treatment over 5 years in 107 patients with blepharospasm, Meige's syndrome, oromandibular dystonia, hemifacial spasm, cervical dystonia, and writer's cramp. Electromyography was used to localize dystonic muscles and guide Dysport injections in Meige's syndrome, oromandibular dystonia, cervical dystonia, and writer's cramp. All but 2 Meige's syndrome and 2 writer's cramp patients responded to treatment. Improvement was dramatic in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
2
8

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 38 publications
4
59
2
8
Order By: Relevance
“…Os efeitos colaterais decorrentes da injeção da toxina botulínica são passageiros. Ptose palpebral é a complicação mais comum (18)(19)(20)(21) . Neste estudo, não houve diminuição da fenda palpebral após aplicação de toxina botulínica.…”
Section: Discussionunclassified
“…Os efeitos colaterais decorrentes da injeção da toxina botulínica são passageiros. Ptose palpebral é a complicação mais comum (18)(19)(20)(21) . Neste estudo, não houve diminuição da fenda palpebral após aplicação de toxina botulínica.…”
Section: Discussionunclassified
“…BoNT treatment trials in oromandibular dystonia (OMD) have been small and/or open label [Blitzer et al 1989;Hermanowicz and Truong, 1991;Van Den Bergh et al 1995;Poungvarin et al 1997;Tan and Jankovic, 1999;Laskawi and Rohrbach, 2001]. The largest prospective openlabel study, concerning 162 patients, reported moderate to excellent improvement in almost 70% of OMD patients.…”
Section: Oromandibular Dystoniamentioning
confidence: 99%
“…Resultados favoráveis do tratamento das distonias focais com ambas as preparações tem sido publicados (10)(11)(12)(13) .…”
Section: Não Cirúrgicounclassified
“…Baseado em unidades de peso, Dysport ® é 16 vezes mais potente do que o Botox ® (40 unidades internacionais (UI) e 2,5 UI por nanograma do complexo toxina-hemaglutinina, respectivamente). Baseado em unidades de atividade biológica, 1 UI de Botox ® é equivalente a 4 UI de Dysport ® (11) .…”
Section: Não Cirúrgicounclassified
See 1 more Smart Citation